2015
DOI: 10.1089/jpm.2015.0177
|View full text |Cite
|
Sign up to set email alerts
|

Preferred and Actual Location of Death: What Factors Enable a Preferred Home Death?

Abstract: This study identifies elements of primary and integrated care that address the gap between preferred and actual place of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 28 publications
3
39
2
6
Order By: Relevance
“…This finding concurs with the results from many previous studies that proved the effectiveness of palliative home care in terms of enabling patients to die at home. 12,[19][20][21] Compared to a meta-analysis by Gomes, 22 our study showed an OR between home visits and home death of 10.29 (95%CI 4.6-22.95), which was higher than the study. The large country variation in the effect of home care on home death can partly be explained by the country's health-care resources, and the organization of end-of-life cancer care likely explains an additional part.…”
Section: Discussioncontrasting
confidence: 75%
“…This finding concurs with the results from many previous studies that proved the effectiveness of palliative home care in terms of enabling patients to die at home. 12,[19][20][21] Compared to a meta-analysis by Gomes, 22 our study showed an OR between home visits and home death of 10.29 (95%CI 4.6-22.95), which was higher than the study. The large country variation in the effect of home care on home death can partly be explained by the country's health-care resources, and the organization of end-of-life cancer care likely explains an additional part.…”
Section: Discussioncontrasting
confidence: 75%
“…Palliative care enables people with life limiting illness to plan and make choices about their end‐of‐life care and place of death . However, in‐hospital death typically occurs contrary to the dying person’s wishes and is associated with higher healthcare expenditures . Four in five Australians desire to die out of hospital, whereas it only occurs for half of decedents .…”
Section: Introductionmentioning
confidence: 99%
“…10 Although studies suggest that as many as 60-80% of adults would prefer to die at home, 13-15 only about one-third of patients (all with chronic life-limiting illness) died at home and over one-third died in an acute care hospital. Prior analyses from our healthcare system show that about 40% of these patients died in the hospital with no significant change between 2010 and 2015.…”
Section: Discussionmentioning
confidence: 99%